The great brain race : how global universities are reshaping the world - Wildavsky, Ben (Princeton University Press, 2012)
In The Great Brain Race, former U.S. News & World Report education editor Ben Wildavsky presents the first popular account of how international competition for the brightest minds is transforming the world of higher education--and why this revolution should be welcomed, not feared. Every year, nearly three million international students study outside of their home countries, a 40 percent increase since 1999. Newly created or expanded universities in China, India, and Saudi Arabia are competing with the likes of Harvard and Oxford for faculty, students, and research preeminence.